Impact of Severe Obesity and Weight Loss on Systolic Left Ventricular Function and Morphology: Assessment by 2-Dimensional Speckle-Tracking Echocardiography. (23rd February 2016) - Karimian, Sevda; Stein, Jürgen; Bauer, Boris; Teupe, Claudius
Abstract : Obesity is associated with an increased risk of heart failure. Little is known about the impact of dietary changes on the cardiac sequelae in obese patients. Twenty-one obese subjects underwent a 12-week low calorie fasting phase of a formula diet. Transthoracic two-dimensional speckle-tracking echocardiography was performed to obtain systolic left ventricular strain before and after weight loss. Body mass index decreased significantly from38.6 ± 6.2 to31.5 ± 5.3  kg/m 2, and the total percentage fat loss was 19%. Weight reduction was associated with a reduction in blood pressure and heart rate. Left ventricular longitudinal global peak systolic strain was in the lower normal range (−18.7 ± 3.2 %) before weight loss and was unchanged (−18.8 ± 2.4 %) after 12 weeks on diet with substantial weight loss. Also, no significant change in global radial strain after weight loss was noted (41.1 ± 22.0 versus43.9 ± 23.3, p = 0.09 ). Left atrial and ventricular dimensions were in normal range before fasting and remained unchanged after weight loss. In our study obesity was associated with normal systolic left ventricular function. A 12-week low calorie diet with successful weight loss can reduce blood pressure and heart rate. Systolic left ventricular function and morphology were not affected by rapid weight reduction.